Function of reactive oxygen species in myeloid-derived suppressor cells - Huang, Jiaojiao; Zhao, Yue; Zhao, Kexin; Yin, Kai; Wang, Shengjun (Frontiers in Immunology, 2023)
Myeloid-derived suppressor cells (MDSCs) are a heterogeneous myeloid cell population and serve as a vital contributor to the tumor microenvironment. Reactive oxygen species (ROS) are byproducts of aerobic respiration and are involved in regulating normal biological activities and disease progression. MDSCs can produce ROS to fulfill their immunosuppressive activity and eliminate excessive ROS to survive comfily through the redox system. This review focuses on how MDSCs survive and function in high levels of ROS and summarizes immunotherapy targeting ROS in MDSCs. The distinctive role of ROS in MDSCs will inspire us to widely apply the blocked oxidative stress strategy in targeting MDSC therapy to future clinical therapeutics.